Analysis of heparanase isoforms and cathepsin B in the plasma of patients with gastrointestinal carcinomas: analytical cross-sectional study - Melo, Carina Mucciolo; Origassa, Clarice Silvia Taemi; Theodoro, Thérèse Rachell; Matos, Leandro Luongo; Miranda, Thaís Aguilar; Accardo, Camila Melo; Bouças, Rodrigo Ippolito; Suarez, Eloah Rabello; Pares, Madalena Maria Nunes Silva; Waisberg, Daniel Reis; Toloi, Giovanna Canato; Nader, Helena Bonciani; et al. (São Paulo medical journal, 2015)
CONTEXT AND OBJECTIVE: Heparanase-1 degrades heparan sulfate and has been correlated with tumor progression. Although the isoform heparanase-2 has no catalytic activity, it seems to be important for modulating heparanase-1 activity. Cathepsin B is a proteinase involved in tumor metastasis. The aim of this study was to analyze heparanase isoform expression and cathepsin B activity in plasma samples from patients with gastrointestinal carcinomas, compared with healthy individuals (control group). DESIGN AND SETTING: This was an analytical cross-sectional study. Peripheral blood samples were collected at a Brazilian public hospital, from 21 patients with histopathological diagnoses of gastrointestinal carcinomas and from 43 healthy individuals. The analyses were performed in two Brazilian medical schools. METHODS: Heparanase isoforms were identified and quantified in plasma samples by means of Western blot. The enzymatic activities of heparanase-1 and cathepsin B were also measured. RESULTS: The results demonstrated that the expression of both heparanase isoforms was significantly greater in plasma samples from gastrointestinal carcinoma patients, compared with the control group. Logistic regression analysis showed that increased heparanase-1 and heparanase-2 expression was exclusively dependent on the tumor. There was a significant increase in heparanase-1 and cathepsin B activity in the patients' plasma. CONCLUSION: Overexpression of heparanase-1 and heparanase-2, along with increased heparanase-1 and cathepsin B activity in plasma, is associated with the diagnosis of gastrointestinal carcinoma. These findings provide support for using non-invasive assays (plasma samples) as an auxiliary method for diagnosing gastrointestinal tumors. CONTEXTO E OBJETIVO: A heparanase-1 degrada heparam sulfato e está relacionada à progressão de tumor. Apesar de a isoforma heparanase-2 não possuir atividade catalítica, parece ser importante para modular a atividade da heparanase-1. A catepsina B é uma proteinase envolvida na metástase de tumores. O objetivo deste estudo foi analisar a expressão das isoformas de heparanase e atividade da catepsina B em amostras de plasma de pacientes com carcinomas gastrointestinais, comparando-se com indivíduos saudáveis (grupo controle). TIPO DE ESTUDO E LOCAL: Este é um estudo transversal analítico. Foram coletadas amostras de sangue periférico, em hospital público brasileiro, de 21 pacientes com diagnóstico histopatológico de carcinoma gastrointestinal e 43 indivíduos saudáveis. As análises foram realizadas em duas faculdades de medicina brasileiras. MÉTODOS: As isoformas da heparanase foram identificadas e quantificadas em amostras de plasma por Western blot. As atividades enzimáticas de heparanase-1 e catepsina B foram também mensuradas. RESULTADOS: Os resultados demonstraram que as expressões das isoformas de heparanase foram significativamente maiores nas amostras de plasma de pacientes com carcinoma gastrointestinal em comparação com o grupo controle. A análise feita por regressão logística mostra que aumento na expressão de heparanase-1 e heparanase-2 é exclusivamente dependente da presença de tumor. Houve aumento significativo na atividade da heparanase-1 e catepsina B no plasma dos pacientes. CONCLUSÃO: A superexpressão de heparanase-1 e heparanase-2, bem como o aumento da atividade de heparanase-1 e catepsina B no plasma, está associada com o diagnóstico de carcinoma gastrointestinal. Tais achados dão suporte ao uso de ensaios não invasivos (amostras de plasma) como método auxiliar para o diagnóstico de tumores gastrointestinais.